Redesign Interior Brand Puratos, Distributor Bakery di Bali - Antonio Gerard Prananta; Sriti Mayang Sari (Intra, 2018)
People in Indonesia this year have started to care about what they consume. This will affect food brands to create new innovations continuously in order to complement the consumer’s needs and desires. It started a competition between several brands in order to get most customers. In addition, through the innovations made, store and office interior also play an important role in attracting consumer’s interest and desires. This brings up the need of interior brand Puratos redesign. The "Welcome Able" concept is used in the design to create a welcoming, homey, colorful & comfy atmosphere in accordance to company’s vision and mission. This design used brown and white dominant neutral color with a little black color and red, yellow, and green as Puratos focal point color. This concept is chosen to make visitors interest and try puratos products so it will increase puratos sales and the brand is known better by the public. By changing the design as well as adding more facilities to the company for visitors and workers, the visitor’s comfort and worker’s performance will certainly increase. This also will make visitors come more often and more interested to come and shop at this brand company.